Impact of Nigeria’s importation of electrical power machinery and iron and steel from South Africa on the manufacturing sector output of Nigeria - Ogechi Hope Njoku (Asha Publishing, 2026)
The study adopted the import-led and export-led growth theories, arguing that imports of capital goods and exports of commodities can stimulate productivity and economic growth. Using a modified Cobb-Douglas production framework and annual time series data from 1996–2023, the study specified an ARDL model, the study specified an ARDL model to examine how Nigeria’s imports of electrical power machinery and iron and steel from South Africa affected manufacturing output. Unit root, cointegration, multicollinearity, autocorrelation, heteroskedasticity, and stability tests were conducted using E-Views 10. The results showed moderate correlations among the variables, with no coefficient exceeding 0.80, indicating absence of multicollinearity. The ARDL lag selection used Akaike Information Criterion, while the Bounds test confirmed cointegration since the F-statistic (4.437013) exceeded the 5% upper bound (3.38), implying a long-run relationship. Long-run estimates revealed that electrical power machinery imports positively influenced manufacturing output, while real exchange rate and GDP growth negatively affected it. In the short run, electrical machinery, iron and steel imports, and exchange rate significantly boosted output. Diagnostic tests confirmed no autocorrelation, no heteroskedasticity, and stable model parameters through the CUSUM test. The study concluded that imports of capital machinery and industrial materials from South Africa contributed positively to Nigeria’s manufacturing sector, especially in the short run. It advised that Nigeria ought to maintain a situation of strategic importation of productive machinery and at the same time encourage production of steel locally, exchange rate stability, infrastructural growth and industrial policies that enhance the local manufacturing capability.